(v) Rehabilitation for shoulder arthroplasty. Issue 5 (October 2015) - Payne, Carol; Jaggi, Anju; Le Leu, Andre; Garofalo, Raffaele; Conti, Marco
Abstract: Shoulder arthroplasty is well established for the treatment of glenohumeral arthrosis, and patients may expect a significant improvement in function and pain relief following surgery. Although there have been advancements in the prosthetics and surgical techniques there is a lack of evidence on the effectiveness of postoperative rehabilitation, which is key to the improvement of functional outcomes in a growing elderly population. Current guidance is based on biomechanical factors and clinical consensus. This paper highlights the challenges that ageing has on soft tissue healing and shoulder function, and the importance of involving the patient early on in the decision making process. It discusses a common approach to the early implementation of exercise-based rehabilitation programme for the anatomic replacement with restoration of normal functional biomechanics, and for the reverse shoulder arthroplasty where there is loss of normal functional anatomy. The programme is initially aimed at protecting healing soft tissues, and ensuring joint stability. It highlights the importance of a team approach to rehabilitation that recognizes the need for effective communication at all stages to guide safe and effective rehabilitation progression. This paper details specific exercises that may be tailored to meet the needs of the individual to optimize functional recovery and promote self-responsibility.